2022
DOI: 10.1093/braincomms/fcac251
|View full text |Cite
|
Sign up to set email alerts
|

Axon hyperexcitability in the contralateral projection following unilateral optic nerve crush in mice

Abstract: Optic neuropathies are characterized by degeneration of retinal ganglion cell axonal projections to the brain, including acute conditions like optic nerve trauma and progressive conditions such as glaucoma. Despite different etiologies, retinal ganglion cell axon degeneration in traumatic optic neuropathy and glaucoma share common pathological signatures. We compared how early pathogenesis of optic nerve trauma and glaucoma influence axon function in the mouse optic projection. We assessed pathology by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…We already observed changes in the CONTRA eyes in our previous study [10] although this was not paired with RGC degeneration; thus, we hypothesize that it could be due to a disruption in the BRB due to OHT-induced damage, which may induce the release of inflammatory signals through the bloodstream to the CONTRA eye. Herein, we propose that signaling through the optic nerve of the OHT eye may also explain the higher microglial activation in the nasal and central areas of the CONTRA eye, as previously reported in a similar model of unilateral ocular damage [32]. Regarding the analysis per retinal layer, the CONTRA eyes only differed from the NAÏVE eyes in both plexiform layers, with these being the two retinal layers with the highest amount of microglial cells, probably having a higher capability to respond to retinal damage than the other layers.…”
Section: Microglial Cellssupporting
confidence: 70%
See 1 more Smart Citation
“…We already observed changes in the CONTRA eyes in our previous study [10] although this was not paired with RGC degeneration; thus, we hypothesize that it could be due to a disruption in the BRB due to OHT-induced damage, which may induce the release of inflammatory signals through the bloodstream to the CONTRA eye. Herein, we propose that signaling through the optic nerve of the OHT eye may also explain the higher microglial activation in the nasal and central areas of the CONTRA eye, as previously reported in a similar model of unilateral ocular damage [32]. Regarding the analysis per retinal layer, the CONTRA eyes only differed from the NAÏVE eyes in both plexiform layers, with these being the two retinal layers with the highest amount of microglial cells, probably having a higher capability to respond to retinal damage than the other layers.…”
Section: Microglial Cellssupporting
confidence: 70%
“…In this regard, despite some studies reporting no affection of Brn3a in the CONTRA eye [ 29 ], some others have reported a slight decrease in the CONTRA eyes in some temporal areas [ 8 ]. These effects in the CONTRA eye have been related to the glial-induced cytokine dysregulation that peaks within this time window [ 8 ], probably due to the inflammatory signals that travel through the optic nerve of the OHT eye and reach the optic nerve of the CONTRA eye, further traveling anterogradely to the retina [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uninjured animals without sham surgery served as controls for all experiments ( Bodeutsch et al ., 1999 ; Panagis et al ., 2005 ; Ananthakrishnan et al ., 2008 ; Macharadze et al. , 2009 ; Liu et al ., 2014 ; McGrady et al ., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The incongruence of AP firing and synaptic currents post-crush suggests that an alternative mechanism underlies AlphaONS RGC dysfunction. Indeed, ONC in one eye can cause changes to the contralateral eye, and in one case RGCs in an uninjured eye showed dysfunction of intrinsic electrical properties ( McGrady et al ., 2022 ). Reduced intrinsic excitability has also been reported in other models of neuronal injury ( Stys et al ., 1992a ; Stys et al ., 1992b ; Waxman et al ., 1992 ; Boal et al ., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previous described [ 32 ]. At the time of use, mice were transcardially perfused with PBS followed by PFA (4%).…”
Section: Methodsmentioning
confidence: 99%